Manufacturing method for laminated piezoelectric materials

JP2026165132APending Publication Date: 2026-10-13KUREHA CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2026054239
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-28
Filing Date
2026-03-27
Publication Date
2026-10-13

Smart Images

  • Figure 2026165132000001_ABST
    Figure 2026165132000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a laminated piezoelectric material having high conductivity, transparency, and piezoelectric properties. [Solution] Piezoelectric constant d 33 A method for manufacturing a laminated piezoelectric material having a pC / N ratio of 10 pC / N or more and 40 pC / N or less, comprising the steps of: preparing a fluororesin piezoelectric film; applying a dispersion containing metal nanowires and an alcohol solvent having a boiling point of 100°C or less, wherein the alcohol solvent content is more than 75.00% by mass, to at least one side of the fluororesin piezoelectric film; and drying the applied dispersion at a temperature of 30°C or more and 110°C or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a method for manufacturing a laminated piezoelectric material. [Background technology]

[0002] Various touch-type input sensors are known that detect user input by touching an operating surface, such as touch panels attached to the displays of electronic devices. These sensors have a laminated piezoelectric body with transparent electrodes on both sides of a piezoelectric film, and detect piezoelectric signals from the transparent electrodes. Such touch-type input sensors require high transparency because it is necessary to accurately perceive the image.

[0003] Traditionally, metal oxide films, such as indium-tin composite oxide (ITO), have been primarily used as transparent electrodes. However, metal oxide films have drawbacks, including high deposition costs and weakness to bending, which hinders the flexibility of the final product. Therefore, there is a need for alternative transparent electrode materials to ITO.

[0004] Silver nanowires are attracting attention as a material for such transparent electrodes. A dispersion containing silver nanowires is applied to a substrate, and then the solvent components are removed by evaporation. As a result, the silver nanowires come into contact with each other on the substrate, forming a conductive network, and a transparent conductor (transparent electrode) can be obtained. Transparent electrodes using silver nanowires have advantages such as excellent transparency, conductivity, and flexibility, as well as the ability to be formed using a wet process and low manufacturing costs.

[0005] Silver nanowires are manufactured by dissolving a silver compound in a polyol solvent such as ethylene glycol, and then precipitating linear metallic silver using the reducing power of the polyol solvent in the presence of a halogen compound and a protective agent such as PVP (polyvinylpyrrolidone) (see, for example, Patent Document 1). Based on these technologies, various dispersions containing improved silver nanowires have been proposed, most of which are aqueous dispersions in which silver nanowires are dispersed in water (see, for example, Patent Document 2).

Prior Art Documents

Patent Documents

[0006]

Patent Document 1

Patent Document 2

Summary of the Invention

Problem to be Solved by the Invention

[0007] The present inventors attempted to form a transparent electrode (conductive layer) using a dispersion liquid containing metal nanowires such as silver nanowires in a laminated piezoelectric body having a fluororesin piezoelectric film. However, according to the studies by the present inventors, when a metal nanowire dispersion liquid containing water as the main dispersion medium is applied to a fluororesin piezoelectric film, poor drying tends to occur. As a result, when the fluororesin piezoelectric film coated with the dispersion liquid is wound into a roll, blocking occurs and part of the coating film peels off, so that sufficient conductivity may not be obtained. In addition, if drying is performed at a high temperature to suppress poor drying, the fluororesin piezoelectric film may be discolored by heat or the piezoelectric property may be deteriorated.

[0008] The present invention has been made in view of the above circumstances, and an object thereof is to provide a method for producing a laminated piezoelectric body having high conductivity, transparency and piezoelectric property.

Means for Solving the Problem

[0009] The present invention relates to the following method for producing a laminated piezoelectric body. [1] Piezoelectric constant d 33A method for manufacturing a laminated piezoelectric material having a density of 10 pC / N or more and 40 pC / N or less, comprising the steps of: preparing a fluororesin piezoelectric film; and applying a dispersion to at least one side of the fluororesin piezoelectric film, the dispersion containing metal nanowires and an alcohol solvent having a boiling point of 100°C or less, wherein the alcohol solvent content is more than 75.00% by mass. The process includes the step of drying the coated dispersion at a temperature of 30°C to 110°C to obtain a conductive layer. Manufacturing method for laminated piezoelectric materials [2] The amount of the dispersion to be applied in the step of applying the dispersion is 3.0 g / m². 2 More than 40.0g / m 2 The following is: A method for manufacturing a laminated piezoelectric material as described in [1]. [3] The drying time in the step of obtaining the conductive layer is 0.3 minutes or more and 6.0 minutes or less. A method for manufacturing a laminated piezoelectric material according to [1] or [2]. [4] The fluororesin piezoelectric film contains a fluororesin whose main component is a constituent unit derived from vinylidene fluoride. A method for manufacturing a laminated piezoelectric material according to any one of [1] to [3]. [5] The metal nanowires include silver nanowires. A method for manufacturing a laminated piezoelectric material according to any one of [1] to [4]. [6] The surface resistivity of the laminated piezoelectric material is 0.1 Ω / sq. or more and 300 Ω / sq. or less. A method for manufacturing a laminated piezoelectric material according to any one of [1] to [5]. [7] b of the laminated piezoelectric material * The value is 3.0 or less. A method for manufacturing a laminated piezoelectric material according to any one of [1] to [6]. [8] The thickness of the conductive layer is 10 nm or more and 450 nm or less. A method for manufacturing a laminated piezoelectric material according to any one of [1] to [7]. [9] The step of applying a curable composition containing a photocurable compound onto the conductive layer, drying and curing it to form an overcoat layer, A method for manufacturing a laminated piezoelectric material according to any one of [1] to [7].

[10] The step of forming at least one of an antistatic layer and a hard coat layer on at least one side of the fluororesin piezoelectric film, wherein the step of applying the dispersion is to apply the dispersion on at least one of the antistatic layer and the hard coat layer. A method for manufacturing a laminated piezoelectric material as described in any of [1] to [9]. [Effects of the Invention]

[0010] According to the present invention, it is possible to provide a method for manufacturing a laminated piezoelectric material having high conductivity, transparency, and piezoelectricity. [Brief explanation of the drawing]

[0011] [Figure 1] Figure 1 is a schematic cross-sectional view showing an example of a multilayer piezoelectric material. [Modes for carrying out the invention]

[0012] 1. Manufacturing method of multilayer piezoelectric material One embodiment of the present invention relates to a method for manufacturing a multilayer piezoelectric material. The laminated piezoelectric material comprises a fluororesin piezoelectric film and a conductive layer. The conductive layer can function as a transparent electrode. The laminated piezoelectric material may also further include other layers as needed. For example, the laminated piezoelectric material may further include an antistatic layer to better prevent static electricity generated during handling, and may further include a hard coat layer or an optical adjustment layer to prevent scratches on the fluororesin piezoelectric film or the antistatic layer, or to adjust the hue. Furthermore, the laminated piezoelectric material may further include an overcoat layer on the conductive layer to reduce the decrease in conductivity due to oxidation of the silver nanowires in the conductive layer, and to further improve durability and scratch resistance.

[0013] Such a laminated piezoelectric material can be manufactured by the following steps: preparing a fluororesin piezoelectric film; applying a dispersion containing silver nanowires to at least one side of the fluororesin piezoelectric film; and drying the applied dispersion to obtain a conductive layer. Each step will be described below.

[0014] 1-1. Process for preparing a fluororesin piezoelectric film Fluorine-based piezoelectric films may be off-the-shelf products or may be manufactured. When manufacturing a fluoro-based piezoelectric film, it can be obtained through a process of forming a fluoro-based film (film formation process), stretching the fluoro-based film (stretching process), and polarization (polarization process).

[0015] (Film forming process) Fluorine-based resin films and fluororesin piezoelectric films are films whose main component is a fluororesin. A fluororesin is a resin obtained by polymerizing an olefin monomer containing at least fluorine. Containing a fluororesin as the main component means that the content of olefin-derived constituent units containing fluorine relative to the total mass of the fluororesin film is 50% by mass or more, preferably 70% by mass or more and 100% by mass or less, and more preferably 90% by mass or more and 100% by mass or less. Furthermore, the content of fluororesin relative to the total mass of the fluororesin film is preferably 50% by mass or more and 100% by mass or less, more preferably 70% by mass or more and 100% by mass or less, and even more preferably 90% by mass or more and 100% by mass or less.

[0016] Fluorine-based resins can be homopolymers or copolymers obtained by polymerizing tetrafluoroethylene (TFE) or vinylidene fluoride (VDF), etc. Examples of fluorine-based resins obtained by polymerizing TFE include copolymers of TFE with one or more substances selected from the group consisting of ethylene, perfluoroalkyl vinyl ether, VDF, 1-chloro-1-fluoroethylene, chlorotrifluoroethylene (CTFE), and hexafluoropropylene (HFP). Examples of fluorine-based resins obtained by polymerizing VDF include homopolymers of VDF, as well as copolymers of VDF with one or more substances selected from the group consisting of 1-chloro-1-fluoroethylene, 1-chloro-2-fluoroethylene, trifluoroethylene, TFE, CTFE, tetrafluoropropene, HFP, and perfluoroalkyl vinyl ether, etc.

[0017] Of these, from the viewpoint of obtaining a fluororesin piezoelectric film with higher piezoelectricity, a fluororesin obtained by polymerizing a monomer containing VDF, i.e., a resin containing constituent units derived from VDF, is preferred. More preferably, as the resin containing constituent units derived from VDF, are a homopolymer of VDF, a copolymer of VDF and trifluoroethylene, a copolymer of VDF and HFP, a copolymer of VDF and TFE, a copolymer of VDF, trifluoroethylene, TFE and CTFE, and a copolymer of VDF, trifluoroethylene, TFE and 1-chloro-1-fluoroethylene, with a homopolymer of VDF being even more preferred. These fluororesins may be used individually or in combination of multiple types.

[0018] The fluororesin preferably contains constituent units derived from VDF as its main component. That is, the olefin monomer containing fluorine is preferably VDF. Containing constituent units derived from VDF as its main component means that the content of constituent units derived from VDF relative to the total mass of the fluororesin is 50% by mass or more, preferably 70% by mass or more and 100% by mass or less, and more preferably 90% by mass or more and 100% by mass or less. Among these, the fluororesin is preferably a VDF homopolymer.

[0019] The content of constituent units derived from VDF contained in fluororesins or fluororesin films is: 19 It can be measured by quantitative analysis using an internal standard with F-NMR.

[0020] Fluorine resin films can be manufactured by any method, such as melt extrusion, hot pressing, or solution casting. Among these, it is preferable to manufacture fluororesin films by melt extrusion, from the viewpoint of obtaining fluororesin piezoelectric films of a certain thickness or greater. For example, fluororesin films can be manufactured by extruding molten fluororesin from a T-die and cooling it by contacting it with a cooling roll.

[0021] (Stretching process) In the stretching process, the manufactured fluororesin film is stretched. The stretching process is preferably performed as needed to increase the proportion of β-type crystals in the fluororesin. β-type crystals have a large polarization structure. The stretching direction may be the TD direction or the MD direction, with the MD direction being more preferable.

[0022] The stretching method is not particularly limited and can be carried out using known stretching methods such as the tenter method or the roll-to-roll method.

[0023] The stretching ratio can be, for example, between 3.0 and 6.0 times. A stretching ratio of 3.0 times or higher makes it easier to adjust the film thickness to a more appropriate range. Furthermore, the β-type crystal transition reaction proceeds sufficiently, leading to higher piezoelectricity and improved transparency. A stretching ratio of 6.0 times or lower further suppresses breakage due to stretching.

[0024] (Polarization process) In the polarization step, a direct current voltage is applied to the fluororesin film to impart piezoelectricity. In the polarization step, a fluororesin piezoelectric film with high piezoelectricity can be obtained by applying a direct current voltage to the fluororesin film in which the proportion of polar β crystals has been increased in the stretching step. The direct current voltage to be applied may be adjusted according to the thickness of the stretched film, and can be, for example, 1 kV or more and 50 kV or less.

[0025] (Fluororesin Piezoelectric Film) The composition of the fluororesin piezoelectric film is the same as the composition of the fluororesin film described above. That is, the fluororesin piezoelectric film preferably contains a fluororesin having a structural unit derived from VDF as a main component.

[0026] Piezoelectric constant d of the fluororesin piezoelectric film 33 may be in a range such that the piezoelectric constant d of the laminated piezoelectric body 33 falls within the range described later. Specifically, the piezoelectric constant of the fluororesin piezoelectric film is preferably 10 pC / N or more and 40 pC / N or less, more preferably 13 pC / N or more and 35 pC / N or less, and still more preferably 15 pC / N or more and 30 pC / N or less. When the piezoelectric constant of the fluororesin piezoelectric film is 10 pC / N or more, the pressure sensitivity can be further enhanced. When the piezoelectric constant of the fluororesin piezoelectric film is 40 pC / N or less, for example, deterioration of surface flatness caused by the polarization treatment is less likely to occur, and appearance defects are less likely to occur.

[0027] The piezoelectric constant of the fluororesin piezoelectric film can be measured in accordance with ISO 19622:2018, which is a test method for the piezoelectric constant d by the direct quasi-static method (d 33 meter method, Berlincourt method). 33 Specifically, using a piezoelectric constant measuring device (for example, Piezometer System PM300 manufactured by PIEZOTEST), a test piece of the fluororesin piezoelectric film is held with a holding force of 1.0 N, and the electric charge generated when an alternating force with a vibration force of 0.15 N and a frequency of 110 Hz is applied is read. The charge measurement is performed on the polarized surface of the film, and the piezoelectric constant is calculated using the absolute value of the measured value. At this time, the value measured within the range including the intersection of the diagonals of the piezoelectric film is the piezoelectric constant d of the fluororesin piezoelectric film. 33 The following applies: If the length of one side of the piezoelectric film is 30 cm or more, a rectangle with sides of 30 cm shall be arbitrarily assumed, and the measurement shall be taken within the range including the intersection of the diagonals of the rectangular film. If both sides of the piezoelectric film are 30 cm or more, a square with sides of 30 cm shall be arbitrarily set on the piezoelectric film, and the measurement range shall be set according to the above method.

[0028] Piezoelectric constant d of fluororesin piezoelectric film 33 This can be adjusted by the type of fluororesin, the polarization treatment, and the stretching treatment conditions. For example, among fluororesins, the more constituent units derived from VDF a resin contains, the higher the piezoelectric constant d of the fluororesin piezoelectric film. 33 It tends to become larger. Also, by strengthening the polarization treatment or stretching treatment, the piezoelectric constant d of the fluororesin piezoelectric film can be increased. 33 It tends to grow large.

[0029] The thickness of the fluororesin piezoelectric film is not particularly limited, but for example, 25 μm to 120 μm is preferred. When the thickness of the fluororesin piezoelectric film is 25 μm or more, the amount of charge generated by the piezoelectric effect increases, making it easier to obtain higher piezoelectricity. The thickness of the fluororesin piezoelectric film is more preferably 30 μm or more, and even more preferably 35 μm or more. When the thickness of the fluororesin piezoelectric film is 120 μm or less, the transparency of the fluororesin piezoelectric film is less likely to be impaired, so 100 μm or less is more preferred, and 80 μm or less is even more preferred. From a similar viewpoint, the thickness of the fluororesin piezoelectric film is more preferably 35 μm to 80 μm.

[0030] The thickness of a fluororesin piezoelectric film can be measured, for example, using a micrometer (JIS C 2151:2019), but it can also be measured by known methods such as using a laser displacement meter, a capacitance displacement meter, or infrared light. At this time, the value measured within the range including the intersection of the diagonals of the piezoelectric film shall be taken as the thickness of the fluororesin piezoelectric film. If the length of one side of the piezoelectric film is 30 cm or more, a rectangle with sides of 30 cm shall be arbitrarily assumed, and the range including the intersection of the diagonals of the rectangular film shall be measured. If both sides of the piezoelectric film are 30 cm or more, a square with sides of 30 cm shall be arbitrarily set on the piezoelectric film, and the measurement range shall be set according to the method described above.

[0031] 1-2. Process of applying metal nanowire dispersion. A dispersion containing metal nanowires and an alcohol solvent with a boiling point of 100°C or lower is applied to at least one side of a fluororesin piezoelectric film.

[0032] Metal nanowires are wire-shaped conductive materials with a diameter on the order of nanometers. The average diameter of metal nanowires is preferably, for example, 1 nm to 500 nm, more preferably 2 nm to 200 nm, and even more preferably 5 nm to 100 nm. The average length of metal nanowires is preferably, for example, 1 μm to 100 μm, more preferably 2 μm to 50 μm, and even more preferably 5 μm to 50 μm. The longer the average length, the more junction points there are between metal nanowires, which can lower the resistance. The smaller the average diameter, the less light scattering by the metal nanowires can be reduced, which can increase the transparency of the conductive layer. The average aspect ratio of metal nanowires is preferably, for example, greater than 5, more preferably 10 or greater, and even more preferably 100 or greater. The aspect ratio is expressed as a / b, where a is the average length and b is the average diameter. a and b can be calculated by measuring the length and diameter of 20 randomly selected metal nanowires using a scanning electron microscope (SEM) and taking their respective average values.

[0033] Examples of metals include at least one selected from the group consisting of gold, silver, platinum, copper, nickel, iron, cobalt, zinc, ruthenium, rhodium, palladium, cadmium, osmium, and iridium, as well as alloys combining these metals. Among these, from the viewpoint of obtaining a conductive layer having low surface resistivity and high total light transmittance, it is preferable to include one or more of gold, silver, and copper, more preferably one or more of gold and silver, and even more preferably silver. In other words, it is preferable for the metal nanowire to include silver nanowire.

[0034] The content of metal nanowires in the above dispersion is not particularly limited, but is preferably 0.05% by mass or more and 0.50% by mass or less, and more preferably 0.10% by mass or more and 0.30% by mass or less, relative to the total mass of the dispersion.

[0035] The alcohol solvent content in the above dispersion is more than 75.0% by mass relative to the total mass of the dispersion. Thus, by containing a high alcohol solvent content in the dispersion, it can be dried at a low drying temperature and in a short time. This suppresses thermal degradation of the fluororesin piezoelectric film, thereby preventing discoloration and a decrease in piezoelectricity. Furthermore, because the dispersion containing a large amount of alcohol solvent has high drying properties, blocking due to poor drying is less likely to occur. Therefore, peeling of the conductive layer and a decrease in conductivity can be prevented. From a similar viewpoint, the alcohol solvent content in the above dispersion is preferably 80.00% by mass or more and 99.95% by mass or less, more preferably 85.00% by mass or more and 99.95% by mass or less, and even more preferably 90.00% by mass or more and 99.95% by mass or less, relative to the total mass of the dispersion.

[0036] As an alcohol solvent with a boiling point of 100°C or lower, those with a lower boiling point are preferable from the viewpoint of quick drying, and alcohols having 1 to 3 carbon atoms are more preferable. Examples of alcohols having 1 to 3 carbon atoms include methanol, ethanol, 1-propanol (n-propanol), and 2-propanol (isopropanol). Among these, ethanol is preferred. These may be included individually or in combination of two or more types.

[0037] Furthermore, the alcohol solvent with a boiling point of 100°C or lower preferably contains a primary alcohol, and more preferably contains a primary alcohol as the main component. In the above dispersion, the content of the primary alcohol relative to the total mass of the alcohol solvent with a boiling point of 100°C or lower is preferably 10.0% by mass or more, and more preferably 85.0% by mass or more and 100% by mass or less. By using a primary alcohol with a boiling point of 100°C or lower as the main component, the drying properties of the above dispersion tend to be improved.

[0038] The above dispersion may further contain water from the viewpoint of adjusting the dispersibility of the metal nanowires. The water content relative to the total mass of the above dispersion is less than 20.0% by mass, preferably between 0.0% by mass and 15.0% by mass, and may be 0.0% by mass.

[0039] The above dispersion may further contain other solvents as needed. Furthermore, the above dispersion may further contain binder resins and various additives.

[0040] The binder resin may be a thermoplastic resin, a thermosetting resin, or a photocurable resin. Examples of the binder resins mentioned above include (meth)acrylic resin, polyester, and ethylene-vinegar. This includes polyethylene glycol, silicone compounds, epoxy resins, etc. These resins may have functional groups such as hydroxyl groups, methylol groups, carboxyl groups, sulfonyl groups, and epoxy groups. This allows the resins to self-crosslink with each other or to be thermally crosslinked via a crosslinking agent.

[0041] Examples of additives include plasticizers, antioxidants, surfactants, thickeners, and organic protective agents. Among these, the dispersion preferably contains a surfactant. The surfactant can be anionic, cationic, nonionic, or amphoteric; examples include sodium dodecyl sulfate (anionic surfactant) and polyethylene glycol monolaurate (nonionic surfactant). Among these, nonionic surfactants are preferred.

[0042] The total content of components other than metal nanowires and solvents (binder resin and various additives) can be, for example, 0.01% by mass or more and 0.10% by mass or less, preferably 0.01% by mass or more and 0.05% by mass or less, relative to the total mass of the dispersion.

[0043] The method of applying the above dispersion is not particularly limited and includes methods such as roll coating, bar coating, dip coating, spin coating, casting, die coating, blade coating, gravure coating, curtain coating, spray coating, doctor coating, screen printing, and inkjet printing.

[0044] The amount of the above dispersion applied should be adjusted so that the thickness of the conductive layer after drying falls within the range described later. For example, the amount of the above dispersion applied is 3.0 g / m². 2 More than 40.0g / m 2 The following is preferable: 5.0 g / m 2 More than 30.0g / m 2 The following is more preferable: 10.0 g / m 2 More than 25.0g / m 2 The following is even more preferable: 10.0 g / m 2 More than 20.0g / m 2 The following is particularly preferred: an application amount of 3.0 g / m². 2 This allows for a more uniform coating thickness. Coating amount: 40.0 g / m² 2 The following conditions can further suppress drying defects.

[0045] Furthermore, a protective film may be attached to the other side of the fluororesin piezoelectric film to which the dispersion is applied (the side opposite to the side to which the dispersion is applied). That is, a step of attaching a protective film to the other side of the fluororesin piezoelectric film may be performed before the step of applying the dispersion. This makes it possible to further improve the flatness of one side of the fluororesin piezoelectric film and to apply the dispersion with a more uniform thickness.

[0046] The protective film can be laminated to the other side of the fluororesin piezoelectric film via an adhesive layer. For example, the release film can be peeled off from the laminated film of release film / adhesive layer / protective film, and the exposed adhesive layer can be pressed against one side of the piezoelectric film to laminate the protective film. The protective film can be laminated at any time, and may be performed between the steps of forming the antistatic layer and the hard coat layer, which will be described later.

[0047] 1-3. A step of drying the above dispersion to form a conductive layer. The coated dispersion is dried at a temperature between 30°C and 110°C (drying temperature). This allows for the formation of a conductive layer containing metal nanowires.

[0048] If the drying temperature is 30°C or higher, the solvent components in the coating film of the dispersion can be sufficiently volatilized and removed. Furthermore, if the drying temperature is 110°C or lower, thermal degradation of the fluororesin piezoelectric film can be suppressed, thereby suppressing discoloration and a decrease in piezoelectricity. From a similar viewpoint, the drying temperature is preferably 30°C to 100°C, more preferably 30°C to 85°C, even more preferably 30°C to 70°C, particularly preferably 30°C to 55°C, and very preferably 35°C to 50°C. Note that the drying temperature refers to the ambient temperature during drying. For example, when drying the coating film in a drying oven, it refers to the set temperature of the drying oven.

[0049] The drying time should be sufficient to allow the solvent components in the dispersion to volatilize and be removed. While this depends on the transport speed and drying temperature, a drying time of 0.3 minutes to 6.0 minutes is preferred, 0.5 minutes to 4.5 minutes is more preferred, and 0.5 minutes to 3.0 minutes is even more preferred. A drying time of 0.3 minutes or more can further suppress drying defects. A drying time of 6.0 minutes or less can further reduce thermal damage to the fluororesin piezoelectric film.

[0050] The drying method is not particularly limited and may include drying by applying hot air, drying by radiant heat, drying using electromagnetic induction, or a combination of these methods. Drying can usually be carried out in a drying oven.

[0051] The thickness of the resulting conductive layer is not particularly limited, but is preferably between 10 nm and 450 nm, and more preferably between 20 nm and 100 nm. A conductive layer thickness of 10 nm or more allows for sufficient conductivity. A conductive layer thickness of 450 nm or less allows for greater transparency of the conductive layer.

[0052] The thickness of the conductive layer can be measured by known methods that involve measuring the thickness from observation of the cross-section of the laminate. The thickness of the conductive layer can be determined by observing the cross-section of the laminated piezoelectric material using a scanning electron microscope (e.g., "SU3800," manufactured by Hitachi High-Tech Corporation) under conditions of an acceleration voltage of 3.0 kV and a magnification of 50,000 times. In this case, the thickness of the conductive layer is measured within a range that includes the center of the surface of the conductive layer (or, in the case of a rectangular laminated piezoelectric body, within a range that includes the intersection of the diagonals), and this value is taken as the representative value. If the length of one side of the piezoelectric film on which the conductive layer is formed is 30 cm or more, or if both sides are 30 cm or more, the measurement range shall be set in the same manner as described above.

[0053] The surface resistivity of the conductive layer is not particularly limited, but it should be within a range that allows the surface resistivity of the laminated piezoelectric material to fall within the range described later. For example, the surface resistivity of the conductive layer is preferably 0.1 Ω / sq. to 300 Ω / sq., more preferably 1 Ω / sq. to 200 Ω / sq., even more preferably 10 Ω / sq. to 150 Ω / sq., and particularly preferably 10 Ω / sq. to 100 Ω / sq. The method for measuring the surface resistivity of the conductive layer can be the same as the method for measuring the surface resistivity of the laminated piezoelectric material described later.

[0054] 1-4. Other processes As described above, the method for manufacturing a laminated piezoelectric material may further include other steps not mentioned above.

[0055] For example, before the step of applying the dispersion, a further step may be performed to form at least one of an antistatic layer and a hard coat layer on at least one side of the fluororesin piezoelectric film. In that case, in the step of applying the dispersion, the dispersion should be applied on at least one of the antistatic layer and the hard coat layer. Alternatively, a further step may be performed to form an overcoat layer on the conductive layer obtained in the drying step of the dispersion.

[0056] 1-4-1. Process for forming an antistatic layer An antistatic layer may be formed on at least one side of the fluororesin piezoelectric film. The antistatic layer can be formed, for example, by applying a composition containing a conductive material and a binder resin to at least one side of the fluororesin piezoelectric film, drying it, and curing it as necessary.

[0057] The conductive material may be an ionic conductive material or an electron conductive material.

[0058] Examples of ion-conducting conductive materials include (a) cationic antistatic agents having cationic groups such as quaternary ammonium salts, pyridinium salts, and primary to tertiary amino groups; (b) anionic antistatic agents having anionic groups such as sulfonic acid bases, sulfate ester bases, phosphate ester bases, and phosphonic acid bases; (c) amphoteric antistatic agents such as amino acid-based and aminosulfate ester-based agents; and (d) nonionic antistatic agents such as amino alcohol-based, glycerin-based, and polyethylene glycol-based agents.

[0059] Examples of electron-conducting conductive materials include conductive polymers and other conductive materials. Examples of conductive polymers include polyacetylene or its derivatives, polythiophene or its derivatives, polypyrrole or its derivatives, polyaniline or its derivatives, etc. Among these, polythiophene or its derivatives are preferred from the viewpoint of high transparency and high conductivity. These conductive polymers may have functional groups such as sulfone groups, amino groups, amide groups, hydroxyl groups, mercapto groups, and carboxyl groups. Examples of conductive materials other than conductive polymers include carbon nanotubes and graphene, etc.

[0060] Among these, it is preferable to include an electron-conducting conductive material, and more preferably a conductive polymer material or carbon nanotube, from the viewpoint of easily lowering the surface resistivity of the laminated piezoelectric material and minimizing bleed-out.

[0061] Examples of binder resins include (meth)acrylic resins, epoxy resins, polyurethanes, polyimides, melamine resins, polyesters, polyvinyl alcohol, polystyrene, polyvinyl acetate, silicone compounds, polyethylene glycol, and the like. These may have functional groups such as hydroxyl groups, methylol groups, carboxyl groups, sulfonyl groups, epoxy groups, and amino groups.

[0062] The above composition may further contain a crosslinking agent as needed. The crosslinking agent should be one that reacts with the functional groups of the resin to cause crosslinking. Examples of crosslinking agents include melamine-based crosslinking agents, polycarbodiimide-based crosslinking agents, polyoxazolidine-based crosslinking agents, polyepoxy-based crosslinking agents, and polyisocyanate-based crosslinking agents.

[0063] Furthermore, the above composition may further contain a diluent as needed. The diluent can be any agent capable of dispersing the resin, and may be water or a water-soluble solvent. Examples of water-soluble solvents include alcoholic solvents such as methanol, ethanol, and isopropyl alcohol.

[0064] Commercially available products can be used as the above-mentioned composition. Examples of commercially available products include a set of conductive coating agent and binder dispersion liquid using the conductive polymer material PEDOT:PSS as the conductive material (e.g., Denatron P-400MP-A, P-400MP-B, etc., manufactured by Nagase ChemteX Corporation), and a set of conductive coating agent and binder resin dispersion liquid using carbon nanotubes as the conductive material (e.g., C-169PF-A, C-169PF-B, etc., manufactured by Nagase ChemteX Corporation).

[0065] The surface resistivity of the antistatic layer is, for example, 1.0 × 10⁻⁶. 4 Ω / sq. or more 1.5×10 10 Preferably less than Ω / sq., and 1.0 × 10⁻⁶ 5 Ω / sq. or more 1.0×10 9 A value of Ω / sq. or less is more preferable.

[0066] The surface resistivity of the antistatic layer can be measured in accordance with JIS C 2139-3-2:2018 using, for example, a high resistivity meter (Hyrestor UX, model number: MCP-HT800, URS probe, manufactured by Nitto Seiko Analytech Co., Ltd.). The measurement is performed over a range including the center of the surface of the antistatic layer (or the range including the intersection of the diagonals in the case of a rectangular laminated piezoelectric material), and the measured surface resistivity is taken as a representative value.

[0067] The thickness of the antistatic layer is not particularly limited, but is preferably, for example, 10 nm to 400 nm. If the thickness of the antistatic layer is 10 nm or more, higher conductivity can be imparted to the laminated piezoelectric material, making it less likely for static electricity to be generated. If the thickness of the antistatic layer is 400 nm or less, discoloration and deterioration of piezoelectricity of the laminated piezoelectric material can be further suppressed. From a similar viewpoint, the thickness of the antistatic layer is more preferably 30 nm to 400 nm, and even more preferably 45 nm to 300 nm.

[0068] The thickness of the antistatic layer can be measured using a spectroscopic interferometric thickness gauge (e.g., Hamamatsu Photonics Optical NanoGauge C13027-11). The thickness of the antistatic layer is measured over a range including the center of the surface of the antistatic layer (or the range including the intersection of the diagonals in the case of a rectangular laminated piezoelectric body), and this value is taken as the representative value. If the length of one side of a rectangular laminated piezoelectric body is 30 cm or more, a rectangle with sides of 30 cm is arbitrarily assumed, and the measurement is taken over a range including the intersection of the diagonals of the rectangular laminated piezoelectric body. If both sides of a rectangular laminated piezoelectric body are 30 cm or more, a square with sides of 30 cm is arbitrarily set on the laminated piezoelectric body, and the measurement range is set according to the method described above.

[0069] 1-4-2. Process for forming the hard coat layer A hard coat layer may be formed on at least one side of the fluororesin piezoelectric film. The hard coat layer can be formed, for example, by applying a curable composition containing a curable compound to at least one side of the fluororesin piezoelectric film, and then drying and curing it.

[0070] (curable compound) The curable compound may be a monomer, oligomer, or polymer. The curable compound may be a thermosetting compound or a photocurable compound, but it is preferably a photocurable compound.

[0071] Photocurable compounds are compounds having photocurable functional groups. Examples of photocurable functional groups include ethylenically unsaturated bonding groups such as (meth)acryloyl groups, vinyl groups, and allyl groups, and ring-opening polymerizable groups such as epoxy groups and oxetanyl groups. Among these, compounds having ethylenically unsaturated bonding groups are preferred, compounds having two or more ethylenically unsaturated bonding groups are more preferred, and polyfunctional (meth)acrylate compounds are even more preferred. (Meth)acrylate refers to either or both acrylate and methacrylate.

[0072] Among polyfunctional (meth)acrylate compounds, examples of bifunctional (meth)acrylate monomers include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxydiaacrylate, bisphenol A tetrapropoxydiaacrylate, and 1,6-hexanediol diacrylate. Examples of trifunctional or more (meth)acrylate monomers include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate. Furthermore, the above (meth)acrylate monomers may have a modified molecular skeleton, and those modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc., can also be used.

[0073] Furthermore, examples of polyfunctional (meth)acrylate oligomers include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate. Urethane (meth)acrylate can be obtained, for example, by the reaction of polyhydric alcohols and organic diisocyanates with hydroxy (meth)acrylate.

[0074] (Polymerization initiator) The curable composition preferably contains a photopolymerization initiator. Examples of photopolymerization initiators include one or more selected from acetophenone, benzophenone, α-hydroxyalkylphenone, Michler ketone, benzoin, benzyl methyl ketal, benzoyl benzoate, α-acyl oxime ester, thioxanthones, etc.

[0075] (Other ingredients) The curable composition may further contain other components as needed. For example, the curable composition may further contain particles to suppress blocking during the manufacture of the laminated piezoelectric material or to adjust the refractive index. The particles may be inorganic or organic.

[0076] Examples of inorganic particles include particles of silica (silicon oxide), titanium oxide, zirconium oxide, aluminum oxide, zinc oxide, and tin oxide, as well as diamond powder, sapphire particles, boron carbide particles, silicon carbide particles, and antimony pentoxide particles. Examples of organic particles include resin particles such as acrylic resin, acrylic-styrene copolymer, and silicone resin. Among these, inorganic particles are preferred because they do not impair the transparency of the hard coat layer, and silica particles are more preferred. The surface of the inorganic particles may be treated with a surface modifier such as a silane coupling agent.

[0077] Furthermore, the curable composition may further contain a diluent. The diluent is preferably one with a polarity similar to that of the particles. Examples of diluents include organic solvents such as alcohols, ketones, esters, carbonates, and aromatics.

[0078] The refractive index of the hard coat layer is not particularly limited, but may be higher than that of the fluororesin piezoelectric film. For example, the refractive index of the hard coat layer is preferably 1.40 or more and less than 1.60, more preferably 1.45 or more and less than 1.60, even more preferably 1.47 or more and 1.57 or less, and even more preferably 1.49 or more and 1.55 or less.

[0079] In this specification, the refractive index refers to the refractive index at a wavelength of 589 nm. The refractive index of each layer can be determined by measuring the psi (Ψ) and delta (△) using a multi-incidence-angle high-speed spectroscopic ellipsometer (e.g., JAWoollam M-2000) and calculating the refractive index at a wavelength of 589 nm from these values.

[0080] The thickness of the hard coat layer is not particularly limited, but is preferably 50 nm or more, more preferably 300 nm to 3000 nm, even more preferably 500 nm to 2000 nm, and particularly preferably 500 nm to 1500 nm.

[0081] 1-4-3. Process for forming the overcoat layer An overcoat layer (protective layer) may be further formed on the resulting conductive layer. This makes the metal nanowires of the conductive layer less susceptible to oxidation and further enhances the durability and abrasion resistance of the conductive layer.

[0082] The overcoat layer can be formed by applying a curable composition containing a curable compound, followed by drying and curing. The curable composition can be the same as that used for forming the hardcoat layer. However, the curable composition must not contain particles such as silica particles. For example, a curable composition containing a photocurable compound, a photopolymerization initiator, a weather resistance enhancer, and a diluent as needed can be used. The photocurable compound, polymerization initiator, diluent, etc., included in the curable composition can also be the same as those described above. Known ultraviolet absorbers and antioxidants can be used as weather resistance enhancers.

[0083] The thickness of the overcoat layer is not particularly limited, but is preferably 30 nm to 500 nm, more preferably 50 nm to 300 nm, and even more preferably 50 nm to 200 nm. The thicker the overcoat layer, the more effectively oxidative degradation of the metal nanowires can be suppressed, and the durability and abrasion resistance of the conductive layer can be further improved. The thinner the overcoat layer, the lower the surface resistivity of the laminated piezoelectric material can be, and poor conductivity can also be suppressed.

[0084] 1-5. Effect According to the above manufacturing method, a conductive layer is formed using a metal nanowire dispersion containing a predetermined alcohol solvent at a high concentration, as described above. Furthermore, the coating film of the dispersion containing metal nanowires is dried at a low drying temperature and for a short time. This suppresses thermal degradation of the fluororesin piezoelectric film, reducing discoloration and a decrease in piezoelectricity. In addition, drying defects are suppressed, thus suppressing blocking and the resulting decrease in conductivity. Therefore, a laminated piezoelectric material with high transparency, piezoelectricity, and conductivity can be obtained.

[0085] 2. Multilayer piezoelectric material As described above, the laminated piezoelectric material includes a fluororesin piezoelectric film and a conductive layer, and may further include one or more of the following: an antistatic layer, a hard coat layer, an optical adjustment layer, and an overcoat layer, as needed. These layers can be combined in any way.

[0086] Figure 1 is a schematic cross-sectional view showing an example of a multilayer piezoelectric material. As shown in Figure 1, the laminated piezoelectric body 10 may include, for example, a first hard coat layer 13B, a fluororesin piezoelectric film 11, an antistatic layer 12, a second hard coat layer 13A, a conductive layer 14, and an overcoat layer 15 in this order.

[0087] The thickness of each layer in the laminated piezoelectric material is as described above. The measurement location is the area including the center of the laminated piezoelectric material (or the area including the intersection of the diagonals in the case of a rectangular laminated piezoelectric material), and the thickness measured within this area is considered representative.

[0088] (Piezoelectric constant) Piezoelectric constant d of a multilayer piezoelectric material 33 The piezoelectric constant d of the laminated piezoelectric material is 10 pC / N or more and 40 pC / N or less, preferably 13 pC / N or more and 35 pC / N or less, and more preferably 15 pC / N or more and 30 pC / N or less. 33 When the piezoelectric constant d of a multilayer piezoelectric material is 10 pC / N or higher, high pressure sensitivity is easily obtained. 33 When the ratio is 40 pC / N or less, the decrease in surface flatness caused by the polarization treatment is less likely to occur, and appearance defects can be further reduced.

[0089] Piezoelectric constant d of a multilayer piezoelectric material 33 This is the direct quasi-static method (d 33 Piezoelectric constant d (by the Meter method and the Berlincoat method) 33 The measurement can be performed in accordance with the test method ISO 19622:2018. Specifically, a piezoelectric constant measuring device (e.g., PIEZOTEST PM300 piezometer system) is used to hold a test piece of the laminated piezoelectric material with a holding force of 1.0 N, and the charge generated when an alternating force of 0.15 N and a frequency of 110 Hz is applied is read. The charge is measured on two surfaces of the laminated piezoelectric material, and the piezoelectric constant d obtained from each surface is read. 33 Of these, the one with the larger absolute value is the piezoelectric constant d of the laminated piezoelectric material. 33 The measurement points on each surface shall be within the range including the center of the surface of the laminated piezoelectric material (or within the range including the intersection of the diagonals in the case of a rectangular laminated piezoelectric material).

[0090] Piezoelectric constant d of a multilayer piezoelectric material 33 This can vary depending on the thermal history of the fluororesin piezoelectric film, for example, due to the drying conditions (drying temperature and drying time) when forming the conductive layer. In particular, when the drying temperature is high, the fluororesin piezoelectric film undergoes thermal degradation, and as a result d 33 The temperature tends to decrease. Therefore, by keeping the drying temperature below a predetermined level, thermal degradation of the fluororesin piezoelectric film is suppressed, and d 33 This makes it easier to adjust the value within the above range.

[0091] (Surface resistivity) The surface resistivity of the laminated piezoelectric material is not particularly limited, but is preferably 0.1 Ω / sq. to 300 Ω / sq., more preferably 1 Ω / sq. to 200 Ω / sq., and even more preferably 10 Ω / sq. to 100 Ω / sq.. When the surface resistivity of the laminated piezoelectric material is 300 Ω / sq. or less, sufficient conductivity can be imparted to the surface of the laminated piezoelectric material, making it easier to detect the piezoelectric signal of the fluororesin piezoelectric film.

[0092] The surface resistivity of a multilayer piezoelectric material can be measured using a resistivity meter (e.g., LorestaGPMCP-T610, manufactured by Nitto Seiko Analytech Co., Ltd.) in accordance with JIS K 7194:1994, employing the DC four-probe method. Since volume resistivity is the product of surface resistivity and thickness, the surface resistivity should be measured in accordance with the method for measuring volume resistivity.

[0093] The surface resistivity of a laminated piezoelectric material is represented by the surface resistivity measured over a range including the center of the side of the laminated piezoelectric material where the conductive layer is located (the surface of the overcoat layer 15 in Figure 1), relative to the fluororesin piezoelectric film (in the case of a rectangular laminated piezoelectric material, this range includes the intersection of the diagonals). For example, if the conductive layer is on the outermost surface, the above measurement should be performed on the surface of the conductive layer; if the overcoat layer on the conductive layer is on the outermost surface, the above measurement should be performed on the surface of the overcoat layer.

[0094] The surface resistivity of a multilayer piezoelectric material can be adjusted by the composition and thickness of the conductive layer, the formation conditions of the conductive layer (e.g., solvent composition, drying temperature, and drying time), and the layer configuration. For example, increasing the content of metal nanowires in the conductive layer or increasing the thickness of the conductive layer can further reduce the surface resistivity of the multilayer piezoelectric material. In addition, increasing the content of the alcohol solvent in the dispersion improves drying properties and further suppresses the increase in surface resistivity of the multilayer piezoelectric material due to blocking. Furthermore, including an antistatic layer in the multilayer piezoelectric material can further reduce its surface resistivity.

[0095] (b * value) b of laminated piezoelectric material * The value is not particularly limited, but for example, 3.0 or less is preferred, -3.0 to 2.0 is more preferred, -1.5 to 1.5 is even more preferred, -1.0 to 1.0 is particularly preferred, and 0.0 to 0.8 is very preferred. * When the value is 3.0 or less, there is less discoloration of the fluororesin piezoelectric film due to heat, and the transparency of the laminated piezoelectric material can be maintained well.

[0096] b of laminated piezoelectric material * This can be measured using a method compliant with JIS Z 8722:2009. Specifically, using a spectrocolorimeter SD7000 (manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS Z 8722:2009, the hue b is measured within the range including the center of the laminated piezoelectric material (the range including the intersection of the diagonals). * Measure the value.

[0097] b of laminated piezoelectric material * The value can be adjusted by the conditions for forming the conductive layer (e.g., solvent composition, drying temperature, and drying time) and the layer structure. For example, by lowering the drying temperature or shortening the drying time when forming the conductive layer, the thermal discoloration of the fluororesin piezoelectric film can be reduced. * The value can be reduced.

[0098] (Total light transmittance) From the viewpoint of application to touch panels, for example, the laminated piezoelectric material preferably has high transparency. Specifically, the total light transmittance of the laminated piezoelectric material is preferably 80% or more, and more preferably 85% or more.

[0099] The total light transmittance of a multilayer piezoelectric material can be measured using a haze meter (e.g., NDH7000SP II, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7361-1:1997. Specifically, the total light transmittance in the area including the center of the surface of the multilayer piezoelectric material (or the area including the intersection of the diagonals in the case of a rectangular multilayer piezoelectric material) is measured using the above method, and this value can be used as a representative value.

[0100] The total light transmittance of a multilayer piezoelectric material can be adjusted by the layer configuration, the refractive index of each layer, and its thickness. For example, including a hard coat layer in the multilayer piezoelectric material can further reduce haze, thereby increasing the total light transmittance. [Examples]

[0101] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.

[0102] 1. Fabrication of multilayer piezoelectric materials 1-1. Fabrication of the laminated piezoelectric body 1 [Fabrication of piezoelectric film] A vinylidene fluoride (PVDF) resin (KF Polymer, manufactured by Kureha Corporation) with a melt viscosity of 2500 Pa·s and a melting point of 173°C was melted using a 50 mm diameter single-screw extruder. The molten resin was filtered through a pleated polymer filter with a filtration accuracy of 20 μm, extruded from a T-die, and cooled in contact with a cooling roll to obtain a PVDF film with a thickness of 160 μm. The PVDF film was guided to a uniaxial stretching apparatus equipped with multiple metal rolls and pinch rolls, and uniaxial stretching was performed at a speed of 4.2 times by adjusting the rotation speed ratio of each roll. Furthermore, a voltage of 11.6 kV was applied from the surface of the film in the thickness direction to obtain a piezoelectric film (fluoropolymer piezoelectric film) with a thickness of 39 μm.

[0103] [Formation of an antistatic layer] On one side of the piezoelectric film described above, a solution was applied using a multi-coater (Hirano Tecseed Co., Ltd.) by mixing a conductive polymer aqueous dispersion P-406A (Nagase ChemteX Corporation), which contains a conductive polymer (PEDOT:PSS) composed of a composite of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid at a solid content concentration of 1.2% by mass, and a binder resin dispersion P-406B (Nagase ChemteX Corporation), which contains a polyester emulsion at a solid content concentration of 20.8% by mass, in a 4:1 ratio. Subsequently, a heat treatment was performed at a drying temperature of 100°C for 0.67 minutes to form an antistatic layer with a thickness of 60 nm.

[0104] The surface resistivity of the above antistatic layer was measured using a high resistivity meter (Nitto Seiko Analytech Co., Ltd., Highrestor UX, model number: MCP-HT800, URS probe) in accordance with JIS C 2139-3-2:2018, and was found to be 1.2 × 10⁻⁶. 8 It was Ω / sq.

[0105] [Formation of the first hard coat layer] A hard coat agent (BS-CH271, manufactured by Arakawa Chemical Industries, Ltd., with an average particle size of amorphous silica of 60 nm) was applied to the piezoelectric film on the side opposite to the antistatic layer using a multi-coater. Subsequently, a heat treatment was performed at a drying temperature of 80°C for 0.5 minutes, followed by an integrated light intensity of 250 mJ / cm². 2 By irradiating with UV light and photocuring, a first hard coat layer with a thickness of 750 nm and a refractive index of 1.50 was formed.

[0106] [Applying protective film] A protective film (polyethylene terephthalate film, Young's modulus 3.8 GPa, thickness 125 μm) was laminated onto the surface on which the first hard coat layer described above was formed, using a laminator, and then wound into a roll to obtain a piezoelectric film with a protective film. The laminator was set to a line speed of 5 m / min and a nip roll contact pressure of 0.3 N.

[0107] [Formation of the second hard coat layer] A hard coat agent (BS-CH271, manufactured by Arakawa Chemical Industries, Ltd., with an average particle size of 60 nm amorphous silica) was applied to the above antistatic layer using a multi-coater. Subsequently, a heat treatment was performed at a drying temperature of 40°C for 1.0 minute, followed by an integrated light intensity of 250 mJ / cm². 2 By irradiating with UV light and photocuring, a second hard coat layer with a thickness of 750 nm and a refractive index of 1.50 was formed.

[0108] [Formation of conductive layer] (Preparation of silver nanowire ink) A silver nanowire ink was prepared containing 0.40% by mass of silver nanowires with an average diameter of 30 nm and an average length of 9.5 μm, 0.10% by mass of other components including a binder resin, organic protective agent, thickener, and surfactant, and 99.50% by mass of ethanol.

[0109] (Preparation of silver nanowire dispersion) The above silver nanowire ink was diluted with a mixed solvent of ethanol and methanol to prepare a silver nanowire dispersion containing 0.19% by mass of silver, 0.05% by mass of a dispersant containing a binder, 86.34% by mass of ethanol, and 13.42% by mass of methanol.

[0110] (Coating and forming of a conductive layer) The silver nanowire dispersion is applied to the second hard coat layer described above at a rate of 16.0 g / m². 2 The material was then coated using a multi-coater. Subsequently, a conductive layer containing silver nanowires with a thickness of 45 nm was formed by drying at a drying temperature of 40°C and a transport speed of 30 m / min for 1.0 minute.

[0111] [Formation of the overcoat layer] (Preparation of dispersion for overcoat) A dispersion for overcoating was prepared by diluting a photocurable resin, mainly composed of urethane acrylate, with methyl ethyl ketone (MEK) to a solid content concentration of 1.5% by mass.

[0112] (Application and formation of the overcoat layer) The above-mentioned overcoat dispersion was applied to the conductive layer using a multi-coater. Subsequently, a heat treatment was performed at a drying temperature of 40°C and a transport speed of 30 m / min for 1.0 minute, followed by an integrated light intensity of 300 mJ / cm². 2 By irradiating with UV light and photocuring, a 100 nm thick overcoat layer was formed, thereby obtaining a laminated piezoelectric body 1.

[0113] 1-2. Fabrication of the laminated piezoelectric body 2 A laminated piezoelectric body 2 was obtained in the same manner as laminated piezoelectric body 1, except that the protective film was laminated to one side of the piezoelectric film, the conductive layer was formed on the piezoelectric film on the side opposite to the protective film layer, and the overcoat layer was formed on the conductive layer.

[0114] 1-3. Fabrication of the laminated piezoelectric body 3 A laminated piezoelectric body 3 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and 2-propanol to a concentration of 13.42% by mass of ethanol and 86.34% by mass of 2-propanol.

[0115] 1-4. Fabrication of the laminated piezoelectric body 4 A laminated piezoelectric body 4 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and water to a concentration of 86.34% by mass of ethanol and 13.42% by mass of water, and that the transport speed for forming the conductive layer was 10 m / min and the drying time was 3.0 minutes.

[0116] 1-5. Fabrication of the laminated piezoelectric body 5 A laminated piezoelectric body 5 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and water to a concentration of 86.34% by mass of ethanol and 13.42% by mass of water, and that in the formation of the conductive layer, the transport speed was 20 m / min, the drying temperature was 80°C, and the drying time was 1.5 minutes.

[0117] 1-6. Fabrication of the laminated piezoelectric body 6 A laminated piezoelectric body 6 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and methanol to obtain a silver concentration of 0.14% by mass, a dispersant containing a binder of 0.04% by mass, ethanol of 83.58% by mass, and methanol of 16.24% by mass, and that in the formation of the conductive layer, a conductive layer with a thickness of 35 nm was formed by drying at a transport speed of 20 m / min for 0.5 minutes.

[0118] 1-7. Fabrication of the laminated piezoelectric body 7 A laminated piezoelectric body 7 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and methanol to obtain a silver concentration of 0.06% by mass, a dispersant containing a binder of 0.02% by mass, ethanol of 78.92% by mass, and methanol of 21.00% by mass, and that in the formation of the conductive layer, a conductive layer with a thickness of 15 nm was formed by drying at a transport speed of 20 m / min for 0.8 minutes.

[0119] 1-8. Fabrication of the laminated piezoelectric body 8 A laminated piezoelectric body 8 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and water to a concentration of 86.34% by mass of ethanol and 13.42% by mass of water, and that in the formation of the conductive layer, the transport speed was 10 m / min, the drying temperature was 100°C, and the drying time was 3.0 minutes.

[0120] 1-9. Fabrication of the laminated piezoelectric body 9 A laminated piezoelectric body 9 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and methanol to obtain a silver concentration of 0.05% by mass, a dispersant containing a binder of 0.01% by mass, ethanol of 77.94% by mass, and methanol of 22.00% by mass, and that a conductive layer with a thickness of 12.5 nm was formed in the formation of the conductive layer.

[0121] 1-10. Fabrication of the laminated piezoelectric body 10 The above silver nanowire dispersion was diluted with a mixed solvent of ethanol and methanol to obtain a silver concentration of 0.10% by mass, a dispersant containing a binder of 0.03% by mass, ethanol of 81.13% by mass, and methanol of 18.74% by mass. Furthermore, in forming the conductive layer, the coating amount was 38.4 g / m². 2 A laminated piezoelectric body 10 was obtained in the same manner as laminated piezoelectric body 1, except that it was dried for 3.0 minutes at a transport speed of 10 m / min to form a conductive layer with a thickness of 60 nm.

[0122] 1-11. Fabrication of the laminated piezoelectric body 11 The silver nanowire dispersion described above was prepared with a silver concentration of 0.40% by mass, a dispersant containing a binder of 0.10% by mass, and ethanol of 99.50% by mass. Furthermore, in the formation of the conductive layer described above, the coating amount was 3.2 g / m². 2 A laminated piezoelectric body 11 was obtained in the same manner as laminated piezoelectric body 1, except that a conductive layer with a thickness of 20 nm was formed by drying at a transport speed of 10 m / min for 3.0 minutes.

[0123] 1-12. Fabrication of the laminated piezoelectric body 12 A laminated piezoelectric body 12 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and 1-propanol to a concentration of 13.42% by mass of ethanol and 86.34% by mass of 1-propanol, and that in the formation of the conductive layer, the transport speed was 10 m / min, the drying temperature was 100°C, and the drying time was 3.0 minutes.

[0124] 1-13. Fabrication of the laminated piezoelectric body 13 A laminated piezoelectric body 13 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and water to a concentration of 75.00% by mass of ethanol and 24.76% by mass of water, and that the transport speed for forming the conductive layer was 4 m / min and the drying time was 7.5 minutes.

[0125] 1-14. Fabrication of the multilayer piezoelectric element 14 A laminated piezoelectric body 14 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and 1-butanol to a concentration of 75.00% by mass of ethanol and 24.76% by mass of 1-butanol, and that the transport speed was 10 m / min and the drying time was 3.0 minutes during the formation of the conductive layer.

[0126] 1-15. Fabrication of the laminated piezoelectric body 15 A laminated piezoelectric body 15 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and water to a concentration of 78.28% by mass of ethanol and 21.48% by mass of water, and that in the formation of the conductive layer, the transport speed was 10 m / min, the drying temperature was 130°C, and the drying time was 3.0 minutes.

[0127] 1-16. Fabrication of the laminated piezoelectric body 16 A laminated piezoelectric body 16 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and 1-propanol to a concentration of 13.42% by mass of ethanol and 86.34% by mass of 1-propanol, and that in the formation of the conductive layer, the transport speed was 10 m / min, the drying temperature was 25°C, and the drying time was 3.0 minutes.

[0128] 1-17. Fabrication of the laminated piezoelectric body 17 A laminated piezoelectric body 17 was obtained in the same manner as laminated piezoelectric body 1, except that the above silver nanowire dispersion was diluted with a mixed solvent of ethanol and 2-propanol to a concentration of 13.42% by mass of ethanol and 86.34% by mass of 2-propanol, and that in the formation of the conductive layer, the transport speed was 10 m / min, the drying temperature was 25°C, and the drying time was 3.0 minutes.

[0129] 2. Evaluation of multilayer piezoelectric materials 2-1.Surface resistivity The surface resistivity of the electrode surface of the fabricated multilayer piezoelectric material was measured using a resistivity meter ("LorestaGPMCP-T610", manufactured by Nitto Seikou Analytech Co., Ltd.) in accordance with JIS K 7194:1994 using the DC four-probe method. Since volume resistivity is the product of surface resistivity and thickness, the surface resistivity was measured in accordance with the method for measuring volume resistivity. The measurement location was defined as the area including the intersection of the diagonals of a rectangular multilayer piezoelectric material, and the surface resistivity of the electrode surface measured within this area was used as a representative value. If an overcoat layer was formed on the electrode, the surface resistivity was measured from above the overcoat layer.

[0130] 2-2.b * value A spectrophotometer (SD7000, manufactured by Nippon Denshoku Industries Co., Ltd.) was used. The measurements were taken in accordance with JIS Z 8722:2009. * The value was measured. Specifically, b in the area including the center of the surface of the multilayer piezoelectric material coated with silver nanowires (in the case of a rectangular multilayer piezoelectric material, the area including the intersection of the diagonals) * The values ​​were measured using the method described above and were used as representative values.

[0131] 2-3. Piezoelectric constant d 33 Piezoelectric constant d in accordance with ISO 19622:2018 33 We measured it. Specifically, a piezoelectric constant measuring device (PIEZOTEST PM300 piezometer system) was used to measure the charge generated when a multilayer piezoelectric test piece was held with a holding force of 1.0 N at a measurement temperature of 25°C, and an alternating force of 0.15 N and a frequency of 110 Hz was applied. The piezoelectric constant of a multilayer piezoelectric material is measured on each of the two surfaces of the multilayer piezoelectric material, and the value with the larger absolute value is used as the piezoelectric constant d of the multilayer piezoelectric material. 33 That's what I decided. The measurement points on each surface were defined as the area including the center of the surface of the laminated piezoelectric material (or the area including the intersection of the diagonals in the case of a rectangular laminated piezoelectric material).

[0132] 2-4.Total light transmittance The total light transmittance of the laminated piezoelectric material was measured using a haze meter (NDH7000SP II, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7361-1:1997. Specifically, the total light transmittance in the area including the center of the surface of the laminated piezoelectric material (or the area including the intersection of the diagonals in the case of a rectangular laminated piezoelectric material) was measured using the method described above, and this value was used as a representative value.

[0133] 2-5. Hayes The haze value of the multilayer piezoelectric material was measured using a haze meter ("NDH7000SP II", manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7136, and the haze measurement result within the range including the intersection of the diagonals of the multilayer piezoelectric material was used as the representative value.

[0134] 2-6. Thickness The thickness of the conductive layer was measured by observing the cross-section of the multilayer piezoelectric material using a scanning electron microscope (Hitachi High-Tech Corporation, SU3800) under conditions of an acceleration voltage of 3.0 kV and a magnification of 50,000x. The thickness of the antistatic layer and the hard coat layer was measured using a spectroscopic interferometric film thickness gauge (Optical NanoGauge C13027-11, manufactured by Hamamatsu Photonics).

[0135] The thickness of each layer was measured using the method described above, within a range that includes the center of each layer's surface (or, in the case of a rectangular laminated piezoelectric material, within a range that includes the intersection of the diagonals), and this value was taken as the representative value.

[0136] Table 1 shows the evaluation results for multilayer piezoelectric materials 1 to 17. In Table 1, EtOH represents ethanol, MeOH represents methanol, IPA represents 2-propanol, 1-PrOH represents 1-propanol, 1-BuOH represents 1-butanol, and H2O represents water. OR indicates that the surface resistivity was too high to be measured. "-" indicates that the measurement was not performed.

[0137] [Table 1]

[0138] As shown in Table 1, the multilayer piezoelectric materials 1-12, obtained by drying a silver nanowire dispersion containing more than 75.00% by mass of an alcohol solvent with a boiling point of 100°C or lower at a temperature of 30°C to 110°C, have lower surface resistivity than multilayer piezoelectric materials 13-14 using a silver nanowire dispersion containing 75.00% by mass or less of an alcohol solvent with a boiling point of 100°C or lower, multilayer piezoelectric material 15 with a drying temperature higher than 110°C, and multilayer piezoelectric materials 16-17 with a drying temperature lower than 30°C. * The low value and high piezoelectric constant indicate that it is possible to achieve both high conductivity and transparency while maintaining good piezoelectric properties. [Industrial applicability]

[0139] According to the present invention, it is possible to provide a method for manufacturing a laminated piezoelectric material having high conductivity, transparency, and piezoelectricity. [Explanation of Symbols]

[0140] 10. Multilayer piezoelectric material 11. Fluorine-based resin piezoelectric film 12. Antistatic layer 13A Second Hard Court Layer 13B First Hard Court Layer 14. Conductive layer 15. Overcoat layer

Claims

1. Piezoelectric constant d 33 A method for manufacturing a laminated piezoelectric material having a density of 10 pC / N or more and 40 pC / N or less, The process of preparing a fluororesin piezoelectric film, A step of coating at least one side of the fluororesin piezoelectric film with a dispersion containing metal nanowires and an alcohol solvent having a boiling point of 100°C or lower, wherein the alcohol solvent content is more than 75.00% by mass. The process includes drying the coated dispersion at a temperature of 30°C to 110°C to obtain a conductive layer. A method for manufacturing a multilayer piezoelectric material.

2. The amount of the dispersion to be applied in the step of applying the dispersion is 3.0 g / m². 2 40.0g / m or more 2 The following is: A method for manufacturing a laminated piezoelectric material according to claim 1.

3. The drying time in the step of obtaining the conductive layer is 0.3 minutes or more and 6.0 minutes or less. A method for manufacturing a laminated piezoelectric material according to claim 1.

4. The aforementioned fluororesin piezoelectric film contains a fluororesin whose main component is a structural unit derived from vinylidene fluoride. A method for manufacturing a laminated piezoelectric material according to claim 1.

5. The aforementioned metal nanowires include silver nanowires. A method for manufacturing a laminated piezoelectric material according to claim 1.

6. The surface resistivity of the laminated piezoelectric material is between 0.1 Ω / sq. and 300 Ω / sq. A method for manufacturing a laminated piezoelectric material according to claim 1.

7. The b of the laminated piezoelectric material * The value is 3.0 or less. A method for manufacturing a laminated piezoelectric material according to claim 1.

8. The thickness of the conductive layer is 10 nm or more and 450 nm or less. A method for manufacturing a laminated piezoelectric material according to claim 1.

9. The process further includes applying a curable composition containing a curable compound onto the conductive layer, drying and curing it to form an overcoat layer. A method for manufacturing a laminated piezoelectric material according to claim 1.

10. The process further includes forming at least one of an antistatic layer and a hard coat layer on at least one side of the fluororesin piezoelectric film, In the step of applying the dispersion, the dispersion is applied on at least one of the antistatic layer and the hard coat layer. A method for manufacturing a laminated piezoelectric material according to claim 1.

Citation Information

Patent Citations

  • Silver nanowire, method for producing the same, water base dispersion product and transparent conductor

    JP2009299162A

  • Methods of nanostructure formation and shape selection

    US20050056118A1